Parietal cortex and movement. I. Movement selection and reaching. - Rushworth, M; Nixon, P; Passingham, R (1997)
Recording studies in the parietal cortex have demonstrated single-unit activity in relation to sensory stimulation and during movement. We have performed three experiments to assess the effect of selective parietal lesions on sensory motor transformations. Animals were trained on two reaching tasks: reaching in the light to visual targets and reaching in the dark to targets defined by arm position. The third task assessed non-standard, non-spatial stimulus response mapping; in the conditional motor task animals were trained to either pull or turn a joystick on presentation of either a red or a blue square. We made two different lesions in the parietal cortex in two groups of monkeys. Three animals received bilateral lesions of areas 5, 7b and MIP, which have direct connections with the premotor and motor cortices. The three other animals subsequently received bilateral lesions in areas 7a, 7ab and LIP. Both groups were still able to select between movements arbitrarily associated with non-spatial cues in the conditional motor task. Removal of areas 7a, 7ab and LIP caused marked inaccuracy in reaching in the light to visual targets but had no effect on reaching in the dark. Removal of areas 5, 7b and MIP caused misreaching in the dark but had little effect on reaching in the light. The results suggest that the two divisions of the parietal cortex organize limb movements in distinct spatial coordinate systems. Area 7a/7ab/LIP is essential for spatial coordination of visual motor transformations. Area 5/7b/MIP is essential for the spatial coordination of arm movements in relation to proprioceptive and efference copy information. Neither part of the parietal lobe appears to be important for the non-standard, non-spatial transformations of response selection.